1969
DOI: 10.1136/jcp.22.5.551
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin B12and folic acid deficiency on small intestinal absorption

Abstract: Three patients are described, and they provide further evidence that deficiency of folic acid and vitamin B12may sometimes affect small intestinal function. Malabsorption of both xylose and vitamin B12returned to normal in one patient after treatment of a megaloblastic anaemia due to dietary deficiency of folic acid. Impaired absorption of vitamin B12was corrected by vitamin B12therapy in the other two patients. The initial cause of the vitamin B12deficiency in one patient was not apparent, but she was taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

1971
1971
1982
1982

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…The dietary history of our patient did not suggest that his folate intake was low. Folic acid deficiency with impaired xylose absorption but without steatorrhoea or other evidence of proximal small bowel dysfunction has been described in an alcoholic female (Forshaw, 1969) and in two patients with malabsorption associated with anticonvulsant therapy (Reynolds et al, 1965). Our patient seems to have been abstemious and there was no history of drug therapy of any kind immediately preceding or during his illness.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The dietary history of our patient did not suggest that his folate intake was low. Folic acid deficiency with impaired xylose absorption but without steatorrhoea or other evidence of proximal small bowel dysfunction has been described in an alcoholic female (Forshaw, 1969) and in two patients with malabsorption associated with anticonvulsant therapy (Reynolds et al, 1965). Our patient seems to have been abstemious and there was no history of drug therapy of any kind immediately preceding or during his illness.…”
Section: Discussionmentioning
confidence: 57%
“…Defective proximal small bowel function with malabsorption of xylose is seen in true pernicious (Addison-Biermer) anaemia, and absorption of vitamin B12 may also be impaired (Carmel & Herbert, 1967;Forshaw, 1969). Minor histological changes in thejejunum have been reported (Foroozan & Trier, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations of intestinal function in nutritional folate deficiency unassociated with alcoholism have yielded conflicting results (Halsted, 1975). Thus, although Forshaw (1969) and Dawson (1971) demonstrated xylose malabsorption in nutritional folate deficiency, which returned to normal after treatment with folic acid, Winawer et al (1965) were unable to detect a functional abnormality. In Kuala Lumpur, Tasker (1961) found that mean xylose excretion after a 5 g oral load was 071 g/5 h in 36 patients with nutritional megaloblastic anaemia, and 1-43 g/5 h in 21 controls.…”
Section: Discussionmentioning
confidence: 96%
“…patients with idiopathic steatorrhoea, and three patients who had had a partial gastrectomy. In the other patient, who has been described previously (Forshaw, 1969), the impaired vitamin B12 absorption was corrected by vitamin B12 and the diagnosis was not certain.…”
Section: Methodsmentioning
confidence: 91%